PROSES HIDROLISIS ASAM DAN ENZIM PADA POLISAKARIDA Euchema cottonii UNTUK BAHAN BAKU BIOETANOL - Pandit Herwono, Dwi Setyaningsih dan Bagus Sediadi Bandol Utomo TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
Indonesia is the second largest exporter of seaweed in the world. It has a promising availability and capacity of producing bioethanol from seaweed. Euchema cottonii is abundantly available in theIndonesian sea which contains high carbohydrate concentration for bioethanol production. This research studied the effect of sulfuric acid concentration for hydrolysis at 121oC and the concentration of cellulase enzyme at different reaction time. The results showed that the best treatment was 1% (v/v) sulfuric acid hydrolysis for 60 min and enzymatic hydrolisis of 5% (v/v) for 12 hours. The reducing sugar content was 5.06% w/v, ethanol yield was 0,55% b/v and fermentation efficiency was 23.47%.Keywords: E. cottonii, acid hydrolysis, enzymatic hydrolysis, bioethanol